Promoting reflection on language learning lessons from a university setting - Curry, Neil; Lyon, Phoebe; Mynard, Jo 1970- (Second language acquisition, 2023)
"This book presents the collaborative efforts of a team of academics at a university in Japan to promote learner reflection. It includes studies, practical applications and reflective accounts, and demonstrates how reflection can be effectively integrated into language learning activities with significant benefits to the learners"--